Genetic Characterization of Human Immunodeficiency Virus type 1 in Elite Controllers: Lack of gross genetic defects or common amino acid changes - Miura, Toshiyuki; Brockman, Mark A.; Brumme, Chanson J.; Brumme, Zabrina L.; Carlson, Jonathan M.; Pereyra, Florencia; Trocha, Alicja; Addo, Marylyn M.; Block, Brian L.; Rothchild, Alissa C.; Baker, Brett M.; Flynn, Theresa; et al. (Journal of Virology, 2008)
Despite reports of viral genetic defects in persons who control HIV-1 in the absence of antiviral therapy, the extent to which such defects contribute to long-term containment of viremia is not known. Most previous studies examining for such defects have involved small numbers, primarily focused on subjects expressing HLA-B57, or have examined single viral genes, and cellular proviral DNA rather than plasma viral RNA sequences. Here we attempted viral sequencing from 95 HIV-1 elite controllers (EC) who maintained plasma viral loads < 50 RNA copies/ml in the absence of therapy, the majority of whom did not express HLA-B57. HIV-1 gene fragments were obtained from 94% (89/95) of the EC, and plasma viral sequences were obtained from 78% (61/78), the latter indicating the presence of replicating virus in the majority of EC. Of 63 persons for whom nef was sequenced, only three cases of nef deletions were identified, and gross genetic defects were rarely observed in other HIV-1 coding genes. In a codon-by-codon comparison between EC and persons with progressive infection, correcting for HLA bias and co-evolving secondary mutations, a significant difference was observed at only three codons in Gag, all three of which represented the historic population consensus amino acid at the time of infection. These results indicate that spontaneous control of HIV replication is not attributable to shared viral genetic defects or shared viral polymorphisms.